Bridging the gap between clinicians and fitness professionals: a challenge to implementing exercise as medicine. Issue 1 (16th October 2018) - Pojednic, Rachele; Bantham, Amy; Arnstein, Fred; Kennedy, Mary A; Phillips, Edward
Abstract : Objective: Health clubs (HC) and personal trainers (PT) are traditional outlets for the promotion of physical activity (PA) and exercise programming. As physicians are increasingly being called on to write exercise prescriptions for their patients, this study sought to investigate the level of integration between the healthcare and fitness systems. Design: An internet study was designed with five domains to understand physicians': (1) overall perception of HC, (2) appropriateness and recommendation of HC and PT to their patients, (3) attitude regarding specific aspects of HC, (4) support of patient participation in HC sponsored exercise and (5) elements of HC that physicians would like to know for referral. Methods: An electronic survey was sent to members of two mailing lists of primary care and sports medicine specialty physicians during 2011–2012. Results: On a Likert scale of 1–10 412 physicians reported being familiar with HC (8.9±2.1), indicated a favourable view of HC (7.9±2.2), and believe HC to be an appropriate venue for their patients (7.5±2.3). However, physicians only recommend HC to 41%±28% of their patients and PT for only 21%±21.6% of patients. Physicians ranked expense and convenience as the most problematic elements of HC (8.1±2.1 and 6.3±2.5, respectively). 72% of physicians indicated cost as most concerning when recommending a specific HC. Conclusion: HC and PT are a significant implementation system for the promotion of physical activity, yet physicians are concerned with several elements of HC and are not adequately relying on this partnership to promote physical activity to their patients.